Kesenjangan Regulasi dan Praktik Perlindungan Konsumen pada Layanan Telemedicine di Indonesia - Claudia Belseran; Hulman Panjaitan; Paltiada Saragi (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Consumer protection in telemedicine services in Indonesia has become increasingly important due to the rapid advancement of technology. These services face risks related to data privacy, unclear consumer rights, and challenges in interactions with healthcare providers. This study aims to evaluate the implementation of consumer rights protection in telemedicine services in Indonesia and analyze the effectiveness of existing regulations in safeguarding these rights. Key issues faced by consumers, such as uncertainties in complaint mechanisms and privacy breaches, are the main focus of this research. The methodology employed is policy evaluation, which includes an analysis of relevant regulations such as the Ministry of Health Regulation No. 20 of 2019 and the Consumer Protection Law. Interviews with legal experts were also conducted to gain deeper insights, along with comparisons to telemedicine regulations in other countries. Findings indicate that despite the existence of regulations, field implementation often does not align with legal provisions. Limitations in supervision and gaps between regulations and on-the-ground practices have resulted in consumer rights violations, particularly concerning data security and complaint mechanisms. Recommendations for improving consumer literacy, strengthening regulations, and establishing stricter monitoring mechanisms are proposed to enhance consumer protection in telemedicine services.